The journalistic collaboration in Internet and the case of ‘The Stream’ Al Jazeera - Renedo Farpón, Cristina (Historia y Comunicación Social, 2014)
The use of new technologies has changed the way people consume and produce information. Internet has democratized content production and created new channels for citizen participation, including major media incorporate these channels to its users. The social networks are also players of this trend. An example of this involvement is The Stream program is aired on Al Jazeera. The program combines public information on digital platforms and professional journalistic treatment of the issues.